Metal-catalyzed reactions in water - Dixneuf, P. H. (Pierre H.); Cadierno, Victorio, 1969- (Weinheim, Germany : Wiley-VCH Verlag & Co. KGaA, 2013)
"This book provides a comprehensive overview of developments in the use of water as a solvent for metal catalysis, illustrating the enormous potential of water in developing new catalytic transformations for fine chemicals synthesis, while reducing environmental impact."--
Metal-Catalyzed Cross-Couplings of Aryl Halides to Form C-C Bonds in Aqueous Media / Kevin H Shaughnessy -- Metal-Catalyzed C-H Bond Activation and C-C Bond Formation in Water / Bin Li, Pierre H Dixneuf -- Catalytic Nucleophilic Additions of Alkynes in Water / Xiaoquan Yao, Chao-Jun Li -- Water-Soluble Hydroformylation Catalysis / Duc Hanh Nguyen, Martine Urrutigoity, Philippe Kalck -- Green Catalytic Oxidations in Water / Roger A Sheldon -- Hydrogenation and Transfer Hydrogenation in Water / Xiaofeng Wu, Jianliang Xiao -- Catalytic Rearrangements and Allylation Reactions in Water / Victorio Cadierno, Joaquin Garcia-Alvarez, Sergio E Garcia-Garrido -- Alkene Metathesis in Water / Karol Grela, Lukasz Gulajski, Krzysztof Skowerski -- Nanocatalysis in Water / R B Nasir Baig, Rajender S Varma.
Online resource; title from PDF title page (viewed May 7, 2014).
Edition statement from first page of chapter PDFs.
Includes bibliographical references and index.
Keywords: Metal catalysts; Organic solvents; Water chemistry; SCIENCE -- Chemistry -- Physical & Theoretical; Metal catalysts; Organic solvents; Water chemistry; Electronic books; Electronic books